If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6y+3=11y+7
We move all terms to the left:
6y+3-(11y+7)=0
We get rid of parentheses
6y-11y-7+3=0
We add all the numbers together, and all the variables
-5y-4=0
We move all terms containing y to the left, all other terms to the right
-5y=4
y=4/-5
y=-4/5
| 72(x+15)=180 | | 10-2j-8=-j+2 | | V=2x(10-x)(15-2x) | | (1/2)r+(1/3)r=5 | | 4c÷5=4 | | 125h=198 | | 3+x5=-17 | | 12+23=-5(5x-7) | | 4(c-73)=20 | | 21x^2=-8 | | -10q-9=-7q | | √2x+4−√x+3=1 | | 2x+10=0.5 | | 32=4a+36 | | √2x+4−√x+3=12x+4-x+3=1 | | 6+9=6n | | 15/11/x=31/3/23/4 | | (r/2)+5r=11 | | 15x+3=16-1 | | 5+5=2(2x+5) | | -3w+26=-6 | | 21x^2+26x=0 | | 0.18/x=0.06/0.09 | | 12x+12=5x+15 | | 12/18=7/x | | 2(x+3)-5(2x-1)=27 | | M+5+m=-1 | | 8+2r=10 | | 4r+9=13r+18 | | −9.5x+0.66=−6.94 | | 14x-21=29+12x | | ((2x+2/3)(3))+((x-2)(4))=(15/2) |